Legal Literacy through Understanding Criminal Procedure Law: The Perspective of the Community and Students of Pancasila and Citizenship Education - Mohammad Masthuro; Arbiana Putri (LPPM STKIP Kusuma Negara, 2026)
This study aims to analyze the role of understanding criminal procedural law in developing legal literacy among Civics (PPKn) students. A qualitative research approach based on descriptive analysis was employed in this study. The researcher employed purposive sampling techniques to interview two law professors and 15 Civics (PPKn) students as research informants. The interactive model of Miles, Huberman, and Saldaña was used to assess data obtained through observation, in-depth interviews, and documentation. As demonstrated by the research findings, understanding criminal procedural law contributes to increased legal knowledge, understanding of legal procedures, the ability to analyze legal cases, and students' legal awareness. This understanding also supports the strengthening of civic competencies that include civic knowledge, civic skills, and civic responsibility. However, the development of legal literacy still faces challenges such as the complexity of legal terms, limited practical experience, and the dominance of unverified legal information from digital media. This study confirms that understanding criminal procedural law is a strategic tool in developing legal literacy among Civics (PPKn) students as prospective educators and agents of legal education in the community.